The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1111/j.1399-3011.2004.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR solution structure of a potent cyclic nonapeptide inhibitor of ICAM‐1‐mediated leukocyte adhesion produced by homologous amino acid substitution

Abstract: We have previously described a disulfide-linked cyclic nonapeptide (inhibitory peptide-01, IP01), with the sequence CLLRMRSIC, which binds to intercellular adhesion molecule-1 (ICAM-1), and blocks binding to its counter-structure, the integrin alphaLbeta2 (leukocyte functional antigen-1, LFA-1) (Sillerud et al., J. Peptide Res. 62, 2003: 97). We now report the optimization of this peptide by means of single homologous amino acid substitutions to yield a new peptide (IP02-K6; CLLRMKSAC) which shows an approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Other laboratories [85][86][87][88][89][90] have synthesized interface peptides based on the binding sequence for ICAM-1 derived from the crystal structure of the complex [91]. We have used NMR to determine the solution structure of our peptides [92], and have docked the most active molecules onto the surface of ICAM-1 in a manner which reveals additional details relevant for the understanding of the relationship between peptide structure and activity [93], particularly the importance of amino acid residues enriched at the sites of protein-protein interaction. Other β2 integrin inhibitors are being pursued after the discovery of an LLG interface peptide sequence [94].…”
Section: Resultsmentioning
confidence: 99%
“…Other laboratories [85][86][87][88][89][90] have synthesized interface peptides based on the binding sequence for ICAM-1 derived from the crystal structure of the complex [91]. We have used NMR to determine the solution structure of our peptides [92], and have docked the most active molecules onto the surface of ICAM-1 in a manner which reveals additional details relevant for the understanding of the relationship between peptide structure and activity [93], particularly the importance of amino acid residues enriched at the sites of protein-protein interaction. Other β2 integrin inhibitors are being pursued after the discovery of an LLG interface peptide sequence [94].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, 10 of 11 peptides (group 4) with the greatest inhibition of SNV infectivity did not have significant sequence relatedness to SNV glycoproteins. Identification of inhibitory peptides that do not have significant sequence relatedness to native ligands has been described in other systems (35)(36)(37), and a large amount of work has indicated that nonhomologous amino acids may mimic the binding activities of each other (reviewed in reference 35). In addition, a comparison of the peptide sequences homologous with SNV to HTNV and PHV glycoproteins did not clearly identify possible contact points of FIG.…”
Section: Vol 79 2005 Peptide Inhibitors Of Snv Entry 7323mentioning
confidence: 99%
“…We chose this approach since we had previously used it successfully to identify inhibitory peptides of other integrin-ligand pairs (35)(36)(37). It is unclear what epitope on ␤ 3 integrin is recognized by ReoPro, and it is likely that antibodies are large enough to prevent interactions with regions well beyond the antibody's own epitope or the virus binding site on ␤ 3 .…”
Section: Vol 79 2005 Peptide Inhibitors Of Snv Entry 7323mentioning
confidence: 99%
“…Another set of interesting ICAM-1-targeting peptides are those derived, as in our work, from molecules that can bind to ICAM-1, such as certain sequences derived from MUC1 mucin core proteins (Hayashi et al, 2001), P(0) CAM (Jaafari and Foldvari, 2002), cyclic peptides derived from the ␣ L ␤ 2 integrin, leukocyte functional antigen-1 (Anderson and Siahaan, 2003;Sillerud et al, 2004). Most of these peptides have also been developed and tested in the context of blocking ICAM-1-mediated adhesion during inflammation and cancer metastasis and have been shown to bind to human ICAM-1 but have not been tested in other species.…”
Section: Discussionmentioning
confidence: 99%